Contribution of Smoke-Belching Vehicles to the Green House Gases Concentration in the City of Dipolog, Philippines - Bernard G. Gilaga; Rowell B. Pallega (Philippine Association of Institutions for Research, Inc., 2012)
Among 212 nations in the world, the Philippines is ranked 48th in terms of carbon emission in the transportation sector. The study sought to determine and estimate the amount of gaseous pollutants emitted by the vehicles in Dipolog City in relation to the overall gaseous pollutants of the Philippines. Results revealed an annual gaseous pollutant contribution of 1,072929.597%V for carbon monoxide and 501,282,073.1 ppm for hydrocarbon emission which, together, roughly explain 6% of the country's overall GHG (Greenhouse gases) output per year. Considering that there are 122 cities in the Philippines, the 6% GHG contribution of Dipolog City is considered well beyond the normal threshold. The study also identified some of the factors leading to this inordinate amount of GHG output of the city, such as, but not limited to: (a) strict implementation of the standards for vehicle emission levels prior to renewal of registration, and (b) strict monitoring and implementation of the anti-smoke belching law or the Clean Air Act (RA 8749).